Polyphenoloxidase from guava (Psidium guajava L.) - Augustin, M.A.; Ghazali, Hasanah M.; Hashim, Hasimah (John Wiley & Sons, 1985)
Polyphenoloxidase (PPO) was isolated from guava (Psidium guajava L., cv. Kampuchea). Purification by acetone precipitation and dialysis of the Amicon concentrate resulted in 4.9‐fold and 17.2‐fold purification of the dialysed crude extract respectively. Polyacrylamide gel electrophoresis indicated that PPO had a molecular weight in the region of 120000–140000. The pH optimum of the enzyme was found to be 7.2. Heat inactivation studies showed that heating for 1.1, 3.5, and 10.1 min at 75, 65 and 55°C respectively caused a 50% loss in enzymic activity. The enzyme‐catalysed browning reaction was significantly inhibited in the presence of sodium metabisulphite, L‐cysteine hydrochloride and ascorbic acid.